Expectation identity for the binomial distribution and its application in the calculations of high-order binomial moments. Issue 22 (17th November 2019) - Zhang, Ying-Ying; Rong, Teng-Zhong; Li, Man-Man
ABSTRACT: For the exponential families normal, gamma, beta, Poisson, and negative binomial, there exists an expectation identity for each of the family. For the binomial family, we discover an expectation identity, which is useful in analytical calculations of its high-order moments.